Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1371/journal.pbio.0050329
|View full text |Cite
|
Sign up to set email alerts
|

GATA3-Driven Th2 Responses Inhibit TGF-β1–Induced FOXP3 Expression and the Formation of Regulatory T Cells

Abstract: Transcription factors act in concert to induce lineage commitment towards Th1, Th2, or T regulatory (Treg) cells, and their counter-regulatory mechanisms were shown to be critical for polarization between Th1 and Th2 phenotypes. FOXP3 is an essential transcription factor for natural, thymus-derived (nTreg) and inducible Treg (iTreg) commitment; however, the mechanisms regulating its expression are as yet unknown. We describe a mechanism controlling iTreg polarization, which is overruled by the Th2 differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
196
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(210 citation statements)
references
References 63 publications
(68 reference statements)
12
196
2
Order By: Relevance
“…GATA3 can interact with FOXP3 (10,11). In Treg cells, FOXP3 interacts with GATA3 to inhibit the expression of the Th-2 cytokines IL-4, IL-5, and IL-13 (12); but unlike GATA3 expression during Th2 polarization, the expression of GATA3 in nTreg cells is independent of STAT6 signaling (5).…”
Section: Important Signaling Loop That Stabilizes the Expression Of Gmentioning
confidence: 99%
See 1 more Smart Citation
“…GATA3 can interact with FOXP3 (10,11). In Treg cells, FOXP3 interacts with GATA3 to inhibit the expression of the Th-2 cytokines IL-4, IL-5, and IL-13 (12); but unlike GATA3 expression during Th2 polarization, the expression of GATA3 in nTreg cells is independent of STAT6 signaling (5).…”
Section: Important Signaling Loop That Stabilizes the Expression Of Gmentioning
confidence: 99%
“…In Treg cells, FOXP3 interacts with GATA3 to inhibit the expression of the Th-2 cytokines IL-4, IL-5, and IL-13 (12); but unlike GATA3 expression during Th2 polarization, the expression of GATA3 in nTreg cells is independent of STAT6 signaling (5). Although GATA3 has been shown to inhibit TGF-␤1-dependent FOXP3 up-regulation during the polarization of induced Treg cells (10), GATA3 and FOXP3 are highly expressed in nTreg cells, and GATA3 expression has been shown to be critical for nTreg cell function. The deficiency of GATA3 specifically in FOXP3 ϩ Treg cells results in the development of spontaneous inflammatory disorders in mice.…”
Section: Important Signaling Loop That Stabilizes the Expression Of Gmentioning
confidence: 99%
“…Furthermore, it was shown that inhibitor of DNA binding 3 À/À T cells were more prone to differentiate into Th17 cells but not into Foxp3 þ Treg cells. 89 The block in Foxp3 expression may be due to Stat6-mediated repression of Foxp3 transcription at its promoter region. 90 Luciferase reporter assays have supported the finding that GATA-3 can bind to the promoter of Foxp3, in order to mediate its transcriptional inhibition, and thus inhibit the differentiation of GATA-3 þ T cells into iTreg cells.…”
Section: Epigenetic and Transcriptional Regulation Of Foxp3mentioning
confidence: 99%
“…An increasing number of studies have identified and proposed a role for Treg in mediating the suppression of allergic airways disease (Stock et al, 2006;Taylor et al, 2006;Tournoy et al, 2006;Hartl et al, 2007;Joetham et al, 2007;Kocks et al, 2007;Larche, 2007;Mantel et al, 2007;Maynard et al, 2007;Niu et al, 2007;Xystrakis et al, 2007;Holt et al, 2008). The proposed mechanisms of Treg-mediated suppression in atopic asthma are thought to involve the immunomodulatory cytokines IL-10 and TGFβ (Taylor et al, 2006) and are summarised in Fig.…”
Section: Regulatory T Cells In Allergic Asthmamentioning
confidence: 99%